Persepsi Guru Dan Siswa Terhadap Penerapan Ice Breaker Di Berbagai Mata Pelajaran - Aperius Gea; Okisman Tafonao (CV. SINAR HOWUHOWU, 2024)
Teachers' and students' opinions about the use of icebreakers in the classroom are investigated in this study. By fostering an enjoyable and engaging learning environment, ice-breaking exercises help students become more motivated, focused, and involved in the process of learning. The findings reveal that ice-breaking positively impacts reducing boredom, alleviating stress, and fostering stronger emotional connections between teachers and students. This technique proves effective across various subjects, both in face-to-face and online classes, helping students to be more prepared and motivated in understanding the material. These results underscore the importance of teacher creativity in selecting innovative teaching methods to optimally achieve learning objectives.